2022
DOI: 10.1519/jsc.0000000000004319
|View full text |Cite
|
Sign up to set email alerts
|

Arousal/Stress Effects of “Overwatch” eSports Game Competition in Collegiate Gamers

Abstract: To date, no physical response data are available for one of the most popular eSport games, Overwatch. The purpose of this investigation was to describe the stress signaling associated with competitive Overwatch play and to understand how acute hormonal responses may affect performance. Thirty-two male college-aged gamers (age: 21.3 6 2.7 years; estimated time played per week: 18 6 15 hours) completed the study. Subjects were randomly assigned to a 6-player team to compete in a tournament-style match. Salivary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The authors also noted the different hormonal response patterns of the tournament participants and stratified them into subgroups according to the observed direction of change in cortisol levels. One of the few studies conducted in the field of esports physiology concerns the relationships between a player's skill level and the hormonal and cardiovascular responses recorded during a match [20]. The authors did not observe differences in cortisol levels between athletes with high and low skills.…”
Section: Introductionmentioning
confidence: 90%
“…The authors also noted the different hormonal response patterns of the tournament participants and stratified them into subgroups according to the observed direction of change in cortisol levels. One of the few studies conducted in the field of esports physiology concerns the relationships between a player's skill level and the hormonal and cardiovascular responses recorded during a match [20]. The authors did not observe differences in cortisol levels between athletes with high and low skills.…”
Section: Introductionmentioning
confidence: 90%
“…A key strength of the present study is that the sample comprised professional esports athletes competing in a Tier 1 league (i.e., Rocket League Championship Series, Season 11) within an established international esports title. Many studies within the esports literature use easier to recruit samples, such as high school (e.g., Moen et al, 2022) and college students (e.g., Kraemer et al, 2022) or high-ranked nonprofessionals (e.g., Poulus et al, 2020), who are less elite and compete within a very different competitive environment compared with professionals. However, the trade-off for recruiting professional esports athletes is that the sample size is smaller.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Leis and Lautenbach (2020) provided an overview of empirical evidence on stress responses in esports, highlighting mixed results on psychophysiological stress related to competitive esports gameplay. Following the authors' call for more research on psychological and physiological stress in esports, studies have demonstrated endocrine and cardiovascular responses during competitive gameplay (e.g., Kraemer et al, 2022;Mendoza et al, 2021). Although research on esports players' experiences (e.g., stressors) and behaviors in esports (e.g., coping) has been increasing over recent years (e.g., Leis et al, 2022;Poulus et al, 2022b;Smith et al, 2019), no study comprehensively addressed research on stressors and coping in esports.…”
Section: Study Purposementioning
confidence: 99%